Comparison of platelet immunity in patients with SLE and with ITP - Lazarus, Alan H; Ellis, Janet; Semple, John W; Mody, Meera; Crow, Andrew R; Freedman, John (Transfusion science, 2000)
Idiopathic thrombocytopenic purpura (ITP) is characterized by the development of a specific anti-platelet autoantibody immune response mediating the development of thrombocytopenia. Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by the production of a wide variety of autoantibodies. In 15–20% of SLE cases, patients develop thrombocytopenia which appears to be autoimmune in nature (SLE-TP). To better understand the pathogenesis of the thrombocytopenia associated with SLE, we investigated the overlapping platelet and cellular immune features between SLE and ITP. Thirty-one patients with SLE, eight with SLE-TP, and 17 with ITP, were studied and compared to 60 healthy controls. We evaluated platelet-associated IgG, platelet microparticles, reticulated platelets, platelet HLA-DR expression, in vivo cytokine levels, lymphocyte proliferation, and the T lymphocyte anti-platelet immune response in these patients. Patients with SLE-TP and those with ITP had increased platelet-associated IgG, an increased percentage of platelet microparticles, a higher percentage of reticulated platelets and larger platelets, suggesting antibody-mediated platelet destruction and increased platelet production. More than 50% of patients with ITP had increased HLA-DR on their platelet surface whereas subjects with SLE-TP did not. Analysis of serum cytokines demonstrated increased levels of IL-10, IL-15 and TNF- α in patients with SLE, but in those with ITP, only increased levels of IL-15 were seen, no increases in any of these cytokines were observed in patients with in SLE-TP. The ability of lymphocytes to proliferate in response to phorbol myristate acetate (PMA) stimulation was increased in SLE-TP, but was normal in both SLE and ITP. Lymphocytes from subjects with ITP displayed an increased ability to proliferate on exposure to platelets, in contrast, those with SLE-TP did not. While the number of subjects evaluated with SLE-TP was small, these data reveal a number of differences in the immunopathogenesis between SLE-TP and ITP.